CULTURAL ADJUSTMENT IN INDONESIAN TEXT’ TRANSLATION “TOBA BATAK TRADITIONAL CEREMONY” INTO ENGLISH - Kresna Ningsih Manik; Berlin Sibarani; Siti Aisyah Ginting; Sri Minda Murni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Cultural adjustments are essential in the translation process, particularly when translating from Indonesian to English, due to the unique cultural nuances, customs, and expressions inherent in each language. Without careful consideration, these elements can easily be lost in translation. One major challenge is the cultural differences between Indonesian and English. Another challenge is the distinction between formal and informal language usage in both languages. To address these challenges, translators need a profound understanding of both the source and target languages and cultures. They must be well-versed in the cultural norms, customs, and expressions of both languages and adapt them appropriately in their translations. This study examines the translation techniques used to achieve cultural adjustments when translating Indonesian texts into English and how these adjustments are realized by the translator. A qualitative approach is employed, specifically descriptive research, aiming to provide a detailed description of existing translations. The data source for this research is the translation work of an English lecturer at the University Prima Indonesia. The translation techniques identified include adaptation, adoption uptake, common/established equivalence, discursive creation, compensation, and variation. The findings indicate that adoption uptake is the predominant technique used by the translator to achieve cultural adjustments from Indonesian to English.